Морфолошки и функционални карактеристики на левата преткомора и левата комора кај возрасна популација - Бушљетиќ, Оливер (Медицински факултет, УКИМ, Скопје, 2020)
Introduction: Aging is a global phenomenon and the adult population over 65 years, and especially over 80 years, is the fastest growing age group. Aging is an internally determined, irreversible and inevitable process of reducing vitality by increasing vulnerability and exposure to various diseases. As a consequence of the aging process, there are significant structural and functional changes in the cardiovascular system that are emphasized in the presence of certain diseases, common in old age. There is no clear boundary between the changes from the "normal" aging process and the pathological changes from the disease. Aim of the study: The aim of our study was to determine the impact of the aging process in different age groups of the elderly population on the symptoms, prevalence and expression of risk factors for atherosclerosis, functional disability and the existence of electrocardiographic disorders registered at rest. To determine the impact of the aging process on echocardiography results, and to determine prognostic factors, on cardiac cavity size, left ventricular (LV) systolic, left atrial (LA), and right ventricular (RV) systolic, and LV diastolic function. Material and methods: According to the established criteria, patients aged 65 years, were divided into three age groups (65-74 years, 75-79 years, ≥80 years). All patients were in sinus rhythm and with left ventricular ejection fraction ≥45%. A two-dimensional (2DE) and three-dimensional (3DE) echocardiographic examination was performed according to the recommendations of the American Society of Echocardiography and the European Association of Cardiovascular Imaging from 2015. Results: We assigned 120 patients, with an average age of 76.1  6.6 years (from 65 to 97 years), of which 62 (51.6%) were women. Our subjects were overweight, mostly with arterial hypertension and diabetes. Fatigue / malaise and dyspnea were major complaints, as symptoms of decreased effort tolerance. Echocardiographic analysis of the left ventricle did not show a significant increase in LV mass but its redistribution, with a decrease in volume. In our 3DE study, we showed that the decrease in the indexed end-diastolic volume of LV continued with age over 80 years. At the same time, systolic function, expressed by the ejection fraction (EF), was preserved but with a reduction in global longitudinal LV deformity, as a more sensitive parameter for initial, preclinical systolic function disorders. Impaired diastolic function of the LV and morphological changes in the LA with aging, consequently increase the maximum volume of the left atrium and decrease its function, expressed by reducing the total longitudinal deformation. Echocardiographic parameters for right heart cavities showed no relationship with age, and there were no changes in the size of the right ventricle and atrium, with preservation of right ventricular systolic function in the oldest group, over 80 years. Age showed a significant negative correlation with self-determined functional capacity, expressed through the value of the Duke Activity Score Index. We received a significant reduction in functional ability and independence in performing daily activities. Diastolic dysfunction has emerged as an independent predictor of lower functional capacity and a basis for diagnosing heart failure with preserved LV EF. Our results on the reproducibility of LA and LV size measurements contribute to the relevance of the application of these measurements in the adult population. Conclusion: For echocardiographic assessment of the adult population, always take into account the impact of the aging process on the size and function of the LV and LA. Appropriate age reference values should therefore be used. To monitor echocardiographic changes that are typical of this population, especially the diastolic function of the LC, due to the significant impact of functional ability in this population.
Докторска дисертација одбранета во 2020 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Љубица Георгиевска Исмаил.